Capacidade combinatória de híbridos comerciais de milho para caracteres agronômicos e bromatológicos da silagem - Gralak, Eliza (2011)
We evaluated eighteen commercial corn hybrids recommended for the South Central region of Parana and eighty-one hybrid combinations obtained between them in a circulant diallel, along with a witness. The objective was to assess the general combining ability (GCA) and specific combining ability (SCA) between eighteen commercial corn hybrids recommended for the South - Central region of Paraná, for agronomic traits and nutritional qualities of silage by selecting Diallel analysis of maize hybrids the best and the best hybrid combinations for the synthesis of new populations in order to produce grain and silage of high nutritional value and investigate correlations among traits. The design was evaluated in 10 x 10 lattice with three replications and each unit consisted of three rows of five meters each, was conducted at the experimental campus in CEDETEG Guarapuava and Farm Touros in Candói. Were evaluated for grain yield, plant height, height of ear insertion in both local and was assessed Guarapuava production of green matter, dry matter production, dry matter, acid detergent fiber, neutral detergent fiber, digestibility in vitro dry matter and crude protein. The first two rows of each plot were evaluated for yield, as well as plant height and height of ear insertion, the third line had been harvested when the grains in the hard dough stage, they were weighed twenty - five plants to obtain production of green, from six plants for silage, and subsequently determining the qualitative characteristics in the laboratory. Data were subjected to analysis of variance and individual and joint diallel analysis. A joint analysis was significant effect of GCA and SCA, there was significance between the GCA x environment interaction for all traits, since the SCA x environment interaction was not significant for grain production. Regarding the GCA effects for feature five hybrids PG SG6015, P30K64, P30B39, and 2B688 GNZ2004 estimates showed positive and high GCA for both sites, since the hybrid CD304 showed the highest negative GCA. Qualitativ e characteristics for the experimental design was randomized blocks with three replications. In diallel analysis was demonstrated genetic variability for all traits. Highlight the hybrids CD304, P30B39, AS1572, AS1560 and P30F53 showed that IVDMD CGC positive and negative for ADF and NDF. For PB the hybrid combinations SG6010 x AS1572, AG5011 x SG6010 e AG8021 x AS1551 were organized in the group of higher crude protein content. Regarding the PMV and PMS iv values found in this study were similar to those reported in literature for the southern region. It can be concluded that the hybrids have evaluated the potential for obtaining the base populations for improvement of maize. Diallel analysis showed to be efficient to identify the best hybrids and the hybrid combinations that yield and qualitative characteristics associated with favorable silage